Modifikasi Permainan Tradisional Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SD Negeri Inpres Perumnas IV, Hedam, Kota Jayapura - Monika Gultom; Yulini Rinantanti; Adolfina Krisifu; Grace Uaga; Afner Saut Sinaga (JURNAL PENGABDIAN PAPUA, 2025)
This community service activity aims to introduce through the use of traditional games modified to suit the characteristics of elementary school children, where play is essentially a child’s world while the development of technological innovation encourages children to play individually or interact less with others and their enviroment. In addition, this community service activity also aims to increase love and pride in traditional games that have cultural content and local wisdom and also have the potential to improve children’s critical thinking skills, because traditional games have been played for generations and always create a sense of unity and beautiful memories until someone is an adult. This community service activities were carried out at SD Negeri Inpres Perumnas IV, located in a residential complex in Heram District, Jayapura city, with 275 students (150 boys and 125 girls) and 12 study groups, located in a land area of 1,551 M2 flanked by residential areas, the GKI Kanaan church, a mosque, and a community health center, making the play space quite narrow for the students. The activity began with an explanation of the origins of the traditional Papuan game oro kino-kino combined with the Simon Says game, followed by an explanation of how to play, cultural values, demonstrations of game modifications, and play sessions.  The results obtained showed that students were motivated to learn and master English, proud to have fun traditional games and can learn while playing and critically determine several English statements to do and not to do, teacherswere motivated to develop more fun and meaningful learning such as using traditional games in their teaching and learning classess of English.